Effects of a genome-wide supported psychosis risk variant on neural activation during a theory-of-mind task - Walter, Henrik; Schnell, Knut; Erk, Susanne; Arnold, Claudia; Kirsch, Peter; Esslinger, Christine; Mier, Daniela; Schmitgen, Mike; Rietschel, Marcella; Witt, Stephanie; Nöthen, Markus Maria; Cichon, Sven; et al. (Molecular psychiatry, 2011)
Schizophrenia is associated with marked deficits in theory of mind (ToM), a higher-order form of social cognition representing the thoughts, emotions and intentions of others. Altered brain activation in the medial prefrontal cortex and temporo-parietal cortex during ToM tasks has been found in patients with schizophrenia, but the relevance of these neuroimaging findings for the heritable risk for schizophrenia is unclear. We tested the hypothesis that activation of the ToM network is altered in healthy risk allele carriers of the single-nucleotide polymorphism rs1344706 in the gene ZNF804A, a recently discovered risk variant for psychosis with genome-wide support. In all, 109 healthy volunteers of both sexes in Hardy-Weinberg equilibrium for rs1344706 were investigated with functional magnetic resonance imaging during a ToM task. As hypothesised, risk carriers exhibited a significant (P<0.05 false discovery rate, corrected for multiple comparisons) risk allele dose effect on neural activity in the medial prefrontal cortex and left temporo-parietal cortex. Moreover, the same effect was found in the left inferior parietal cortex and left inferior frontal cortex, which are part of the human analogue of the mirror neuron system. In addition, in an exploratory analysis (P<0.001 uncorrected), we found evidence for aberrant functional connectivity between the frontal and temporo-parietal regions in risk allele carriers. To conclude, we show that a dysfunction of the ToM network is associated with a genome-wide supported genetic risk variant for schizophrenia and has promise as an intermediate phenotype that can be mined for the development of biological interventions targeted to social dysfunction in psychiatry.
Online veröffentlicht 16 March 2010
Gesehen am 07.11.2022